2021
DOI: 10.1016/j.rmed.2021.106489
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of inhaled surfactant in patients with COVID-19-associated acute respiratory distress syndrome

Abstract: Background We have investigated the use of nebulized surfactant as a potential therapeutic option for the patients with coronavirus disease 2019 (COVID-19)-associated acute respiratory distress syndrome (ARDS) undergoing non-invasive ventilation. Methods The patients were divided into 2 groups: surfactant (n = 33) and control (n = 32). The subjects in the surfactant group received the inhaled surfactant at daily dose of 150–300 mg. The oxygenation parameters and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“… 438 Several studies have investigated the effects of surfactant therapy in patients with COVID-19-induced ARDS. The results were encouraging, 439–441 contrary to the effect of surfactant replacement therapy in ARDS patients. This difference might be attributed to the fact that COVID-19-induced ARDS is pathophysiologically different from ARDS, and has more common elements with neonatal respiratory distress syndrome.…”
Section: Clinical Acute Lung Inflammation - Acute Respiratory Distres...mentioning
confidence: 77%
“… 438 Several studies have investigated the effects of surfactant therapy in patients with COVID-19-induced ARDS. The results were encouraging, 439–441 contrary to the effect of surfactant replacement therapy in ARDS patients. This difference might be attributed to the fact that COVID-19-induced ARDS is pathophysiologically different from ARDS, and has more common elements with neonatal respiratory distress syndrome.…”
Section: Clinical Acute Lung Inflammation - Acute Respiratory Distres...mentioning
confidence: 77%
“…Surfactant-BL has been approved by the Ministry of Health of the Russian Federation for clinical use since 2000. The main advantage of this preparation is a very close similarity to lipid/protein composition of human pulmonary surfactant (see Table S1 in the Supporting Information) that ensures high efficiency of Surfactant-BL in the treatment of lung pathologies not only in newborns, but also in adult patients. Recently, the wide therapeutic benefits of inhaled application of Surfactant-BL has been demonstrated in patients with COVID-19-associated acute respiratory distress syndrome …”
Section: Resultsmentioning
confidence: 99%
“…therapeutic benefits of inhaled application of Surfactant-BL has been demonstrated in patients with COVID-19-associated acute respiratory distress syndrome. 48 Surface pressure−area isotherms of Surfactant-BL were measured on a commercially available trough (Model KSV-5000, KSV NIMA, Finland). The surfactant preparation was suspended in chloroform at a concentration of 0.47 mg/mL; the solution was spread on the surface of pure water (Milli-Q Water Purification System, Millipore) in a Langmuir trough.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A particular case of recent interest has been the potential use of SRT in the treatment of COVID-19 patients [ 126 ]. Preliminary results upon application of SRT in some COVID-19 patients were encouraging [ 127 , 128 ] and several clinical trials are open at the time of writing this review, whose results should be delivered in brief allowing to assess the potential utility of surfactant replacement to improve the outcome of patients with severe COVID-19-associated ARDS. It has been reported that the SARS-Cov-2 virus has some tropism against type II cells, whose destruction is a probable contribution to the severity of the worst cases of COVID-19.…”
Section: Tailoring Surfactants For Specific Applicationsmentioning
confidence: 99%